Strawberries for sale in Rovaniemi, Finland in June 2018 ... - Campbell, Sandy (University of Alberta Library, 2018)
These strawberries were for sale at a table outside the K Supermarket in Rovaniemi, Finland in June 2018. The berries on the left are Finnish grown, while the smaller ones in the baskets on the right were grown in Sweden. The word "Ruosti" is an archaic word meaning "Swede". The Finnish berries, while larger are more than the twice as expenisveat 6 Euros for 1/2 litre or 250g as the Swedish berries are 5.50 Euros/litre. Both are called Makeat Mansikat (sweet strawberries). ...